Peningkatan Kapasitas Peternak Sapi Bali Dalam Pengolahan Pakan Fermentasi Di Kel. Malino, Kec. Tinggimoncong, Kab. Gowa, Sulawesi Selatan - Said, Muhammad Irfan; Syawal, Sutomo; Asriany, Anie (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Increasing livestock productivity can be done through efforts to improve livestock nutrition and environment. The basic problem faced by partners is a lack of feed in certain seasons and the production of quite large amounts of fecal waste. In this case, universities, as one of the institutions responsible for providing solutions, of course feel the need to take "action". This activity can be implemented in the form of technology transfer, especially related to the issue of animal feed and waste. This activity aims to increase the capacity of members of the farmer-livestock group "Abbulosibatang" in the Batulapisi Dalam village, Malino Sub-District, Tinggimoncong District, Gowa Regency, especially in processing fermented feed. This activity is a manifestation of the university's concern for the condition and productivity of people's livestock businesses which are increasingly declining. Technology applied activities have been successfully implemented in the Batulapisi Dalam village , Malino Sub-District, Tinggimoncong District, Gowa Regency, South Sulawesi. The partner involved is the farmer-livestock group "Abbulosibatang". One of the technology packages that has been disseminated is rice and corn straw "silage" fermented feed technology. Technology applied methods are carried out through face-to-face and practical training activities. Next, assistance and monitoring efforts are carried out. The results of the implementation of activities show that technology application activities have a very positive impact on partners in increasing capacity, especially related to the ability to process and produce fermented feed as reserve feed in certain seasons.